Consecutive Sonogashira–Suzuki–Michael Cyclization: Three-Component Synthesis of Phenanthridines and Benzo[c]chromenes - Schmitz, G. Hendrik; Karl, Leonard; Ganter, Christian; Müller, Thomas J. J. (Synthesis, 2025)
The equistoichiometric three-component reaction of an acid chloride, an alkyne, and an ortho-amino- or ortho-hydroxyphenylboronic ester proceeds smoothly to give phenanthridines or benzo[c]chromenes, respectively, with good to quantitative yields in the sense of a Sonogashira–Suzuki–Michael cyclization sequence. In the coupling of ortho-amidophenylboronates, interestingly, after ring closure a subsequent an acyl migration occurs to give 6-(2-(acyloxy)vinyl)phenanthridines.
Keywords: alkynylation; catalysis; multicomponent reaction; Michael addition; phenanthridines; benzo[c]chromenes; rearrangement; palladium